HGG-11. Clinical characteristics and clinical evolution of a large cohort of pediatric patients with primary central nervous system (CNS) tumors and tropomyosin receptor kinase (TRK) fusion. (3rd June 2022) - Lamoureux, Audrey-Anne; Fisher, Michael; Lemelle, Lauriane; Pfaff, Elke; Kramm, Christof; De Wilde, Bram; Kazanowska, Bernarda; Hutter, Caroline; Pfister, Stefan M; Sturm, Dominik; Jones, David; Orbach, Daniel; et al.
Abstract: BACKGROUND: TRK fusions are detected in less than 3% of CNS tumors. Given their rarity, there are limited data on the clinical course of these patients. METHODS: We contacted 166 oncology centers worldwide to retrieve data on patients with TRK fusion-driven CNS tumors. Data extracted included demographics, histopathology, NTRK gene fusion, treatment modalities and outcomes. Patients less than 18 years of age at diagnosis were included in this analysis. RESULTS: Seventy-three pediatric patients with TRK fusion-driven primary CNS tumors were identified. Median age at diagnosis was 2.4 years (range 0.0–17.8) and 60.2 % were male. NTRK2 gene fusions were found in 37 patients (50.7%), NTRK1 and NTRK3 aberrations were detected in 19 (26.0%) and 17 (23.3%), respectively. Tumor types included 38 high-grade gliomas (HGG; 52.1%), 20 low-grade gliomas (LGG; 27.4%), 4 embryonal tumors (5.5%) and 11 others (15.1%). Median follow-up was 46.5 months (range 3-226). During the course of their disease, a total of 62 (84.9%) patients underwent surgery with a treatment intent, 50 (68.5%) patients received chemotherapy, 35 (47.9%) patients received radiation therapy, while 34 (46.6%) patients received NTRK inhibitors (3 as first line treatment). Twenty-four (32.9%) had no progression including 9 LGG (45%) and 9 HGG (23.6%). At last follow-up, only one (5.6%-18 evaluable) patient with LGG died compared to 11 with HGG (35.5%-31 evaluable). For LGG the median progression-free survival (PFS) after the first line of treatment was 17 months (95% CI: 0.0-35.5) and median overall survival (OS) was not reached. For patients with HGG the median PFS was 30 months (95% CI: 11.9-48.1) and median OS was 182 months (95% CI 20.2-343.8). CONCLUSIONS: We report the largest cohort of pediatric patients with TRK fusion-driven primary CNS tumors. These results will help us to better understand clinical evolution and compare outcomes with ongoing clinical trials.